How are water treatment technologies used in developing countries and which are the most effective? An implication to improve global health - Zinn, Caleb; Bailey, Rachel; Barkley, Noah; Walsh, Mallory Rose; Hynes, Ashlen; Coleman, Tameka; Savic, Gordana; Soltis, Kacie; Primm, Sharmika; Haque, Ubydul (Journal of Public Health and Emergency; Vol 2 (September 2018): Journal of Public Health and Emergency, 2018)
Worldwide, there are an estimated 2.3 billion people living in water-scarce and stressed areas. The water in these areas may contain harmful pathogens, such as bacteria, that can have a negative effect on human health. Poor sanitation, lack of hygiene, contaminated water sources, and the overall poor quality of drinking water leads to disease and death amongst people of all ages in underdeveloped and developing countries. In order to better the health of these communities and the quality of water, affordable water treatment technologies that can reduce harmful contamination to potable water standards must continue to be developed. The purpose of this study is to review the currently available techniques, such as solar water disinfection (SODIS), chlorination, ceramic and biosand water filtration and slow sand filtration, that can be utilized in developing countries. A number of peer-reviewed journal articles were reviewed to identify the strengths and weaknesses of each of water treatment technologies. This process is based on the quality/efficiency of the treatment process, the availability/accessibility of the treatment as well as its overall effectiveness. Based on our study, SODIS had the most positive impacts however, membrane filtration shows a potential to become the preferred water treatment method in the future. Affordable and effective water treatment is a vital step towards reducing morbidity, as well as reducing health complications for the present and the future in developing countries.